Modeling and optimization of catalyst concentration and reaction temperature on yield and calorific value of biodiesel from CPO. Issue 1 (April 2021) - Hendrawan, Y; Daisy,; Utami, R; Nurseta, D Y; Yudho, R; Argo, B D; Susilo, B
Abstract: In this research, response surface methodology (RSM) has been developed with a central composite design (CCD) model using two input variables i.e. KOH concentration and the reaction temperature, and two responses i.e. biodiesel yield as quantity parameter and calorific value as quality parameter. RSM optimization result showed a parabolic curve with a maximization function with a quadratic mathematical model. Mathematical model that had been given for yield response was Y1 = - 361.75066 + 298.06346X1 + 15.36142X2 + 0.5X1 X2 – 159.4X1 2 – 0.14463X2 2, where: Y = Yield response, X1 = KOH concentration (% w/v), X2 = reaction temperature (°C), meanwhile the mathematical model for calorific value response was Y2 = 21534.81810 + 2163.76029 X1 – 487.60022 X2 + 69.11980 X1 X2 - 2709.22080 X1 2 + 3.84021X2 2 . The optimum solution obtained by RSM was a KOH concentration of 1.08% (w/v) and reaction temperature at 60.11°C. Validation data indicated that the actual value (obtained by experimental result) was similar to that of the prediction value (obtained from RSM). Meanwhile, biodiesel characteristics that had been produced included: viscosity 7.356 cst, water content 5.6%, density 0.864 g/ml, a flashpoint at 135°C, yield 210.90 ml, and calorific value is 9864.834 cal/g.